African and Asian Medicinal Plants as a Repository for Prospective Antiviral Metabolites Against HIV-1 and SARS CoV-2: A Mini Review - Godwin Anywar; Muhammad Akram; Muhammad Amjad Chishti (Frontiers Media S.A., 2021)
Introduction: The worldwide burden of viral infections has triggered a resurgence in the search for new and more efficient antiviral drugs. Scientists are also repurposing existing natural compounds such as the antimalarial drug artemisinin from Artemesia annua L. as potential drug candidates for some of the emerging and re-emerging viral infections such as covid-19Aim: The aim of this review was to analyse the existing literature to explore the actual or potential natural antiviral compounds from African and Asian medicinal plants as lead compounds in the drug discovery process.Methods: We searched the literature on African and Asian medicinal plant species as antiviral agents for HIV-1 and the novel coronavirus (SARS-CoV-2) in various databases and search engines such as Web of Science, Google Scholar and PubMed. The search was limited to in vitro, in vivo, and clinical studies and excluded in silico studies.Results: We present 16 plant species with actual or potential antiviral activity against HIV-1 and SARS-CoV-2. These plant species span the continents of Africa and Asia where they are widely used for treating several other ailments.Conclusion: Natural compounds from plants can play a significant role in the clinical management of HIV/AIDS and the covid-19 pandemic. More research needs to be conducted to investigate the potential toxicities of the various compounds and their efficacies in clinical settings.